Inquérito de violências e acidentes em serviço de referência hospitalar de Sergipe - Lima, Shirley Verônica Melo Almeida (2013)
Violence and accidents have a major impact on the health conditions of the population and its effects go beyond individual and collective suffering, because they reach a much larger number of people than those who are directly involved. The approach of violence and accidents by Public Health is crucial in order to obtain the greatest possible knowledge and unite, data, on its extension, characteristic and consequence. The study aimed to describe the occurrence of violence and accidents and learn the spatial distribution of cases by the municipalities of occurrence. This is an descriptive, transversal study with a quantitative approach, developed in a reference Hospital for the central south region of Sergipe. The study population was composed of all the victims of violence and accidents (N=1065) admitted to the Regional Hospital for 30 consecutive days, on all shifts with application of the Surveillance Survey for Violence and Accidents by the Ministry of Health. Of the 1065 women interviewed typified occurrences were found in transport accidents with 363 victims (34.1%), fall with 313 (29.4%), assault / abuse with 58 (5.4%), burns 08 (0.8%) with self-harm 04 (0.4%) and other accidents 319 (30.0%). The average age of the victims was 30 years (SD: 20.8) the majority were male 705 (66.2%), color - brown skin 538 (50.5%) and low education level (58.1%). As to the location and nature of the injury, was more frequent the upper limbs (35.7%), lower limbs (32.6%) followed by the region of the head/face (16.5%) and natures such as contusion/fracture (45.2 %) and cut/laceration (36.7 % ). The outcome revealed that almost all of the victims 995 (93.4%) progressed to hospital discharge. The associations between the type of accident, the gender of the victims and the location injuries were statistically significant when compared to the age groups. The spatial distribution by municipalities of occurrence was not limited to the south central region of the state, being that there was caring for victims of violence and accidents from other regions. It was concluded that there was a great demand for treatment at specialist centers for violence and accidents that exceeded the defined and health care region and overloaded the institution, although the shortness of duration of hospitalization signal minor injuries. The study contributes to guide public policies aimed at preventing and reducing these injuries that are configured as a public health problem.